Experimental investigation and performance of timber-concrete composite floor structure with non-metallic connection system. (15th August 2019) - Daňková, J.; Mec, P.; Šafrata, J.
Highlights: The connection system is strong and also has the ability ductility. The composite effect is evident when activating the connection system. The design model, γ-analysis, understands the performance of the structure. Abstract: This paper presents results of an experimental study implemented with the goal to verify performance of an innovative type of a timber-concrete composite floor structure. It is unique because the connections of both parts of the composite T-cross-section are assembled from non-metallic materials only. The connection element is a glued board made of plywood. Experimentally, by a shear test, values of secant slip modulus were determined at 12 samples in total. Results of shear tests were analysed by exploratory statistical methods. This method of connection has a medium level of rigidity when loaded with shear force and compared to other types of connection. However, at the same time it manifests a significant area of plastic deformations at higher levels of load. Part tests were carried out with 3 samples, each of which was subject to various levels of environmental effects and a load time before the test. Results were compared with results of the test performed with a reference sample – a non-composite structure of identical dimensions. Experimental data were compared with data provided by the theoretical design model as stated in Eurocodes. The comparison relates to short-term behaviour of the structure. This article also includes consideration of a comparison with the performance of the HBV® System type structure. With the part span of 6.5 m, the final maximum short-term resistance of the timber-concrete composite structure was approximately 200 kN and the maximum average mid-span deflection was approximately 54 mm. For a structure exposed for the period of 12 months to an outdoor environment with the load action for 166 days with the intensity of 10 kN/m 2, the final short-term resistance of the timber-concrete composite structure was higher by 21% than that of a non-composite structure of identical dimensions.